COMPREHENSIVE ANALYSIS OF THE ABSORPTION LITHIUM BROMIDE REFRIGERATING MACHINE AS PART OF THE CCGT-110 AND ALBRM POWER SYSTEM - L. V. Galimova; D. Z. Bayramov (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. The use of an absorption lithium bromide refrigerating machine  for cooling the cycle air before the gas turbine unit of a combined-cycle gas  turbine in a hot climate has proven its effectiveness. It is essential to  maintain the design values for which constant monitoring is carried out and  the operation parameters are adjusted. The objective of this work is to  conduct a comprehensive analysis of the absorption lithium bromide  refrigerating machine as part of an energy-saving system. Methods. As a research method, the method of energy and exergetic  analysis based on the results of a full-scale production experiment was  adopted. Results. The energy analysis was performed using the ξ-i diagram for a solution of lithium bromide with water. According to the energy analysis results, deviations in the work of the absorption lithium bromide  refrigerating machine were revealed, and the exergetic analysis confirmed these deviations. Conclusion. The analysis of the operation of the absorption lithium bromide refrigerating machine allowed identifying deviations in work and their causes.